Monkeypox stigma and risk communication; Understanding the dilemma - Weam M. Banjar; Meshal K. Alaqeel (Elsevier, 2024)
Monkeypox (MPX) is a viral zoonotic disease that is endemic in Central and West African countries had affected countries in Asia, Europe, Africa, Australia, and South and North America. Some globally reported cases were linked to history of recent travel to endemic regions, however, official reports revealed homosexual practices among the majority of reported cases. In response to global increase MPX burden and number of cases, the WHO declared MPX a Public Health Emergency with International Concern (PHEIC) on July 23, 2022. The first MPX case in Saudi Arabia was a returning traveler from Europe to Riyadh on July 14, 2022. It is essential for policy makers to maintain neutral tone for health education messages and inform the public that MPX transmits via physical contact.